CHARACTERIZATION OF QUANTITATIVE PROPERTIES OF MALE AND FEMALE DUCKS UNTIL 4 MONTHS AGE - Depison, Depison (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
The purpose of this study was to determine the quantitative characteristics of male and female Kerinci ducks until the age of 4 months. The research material was 72 Kerinci ducks consisting of 36 males and 36 females. The method used is the experimental method. The data collected included body weights at DOD, 1, 2, 3, and 4 months, body weight gain at DOD-1, 1-2, 2-3, and 3-4 months and body measurements at 4 months. The data on body weight, body weight gain and body size measurements of males and females were analyzed using the t-test. Regression and correlation analysis were used to see the relationship and the close relationship between DOD weight and body weight. Body size and shape characteristics were analyzed using Principal Component Analysis (AKU). The results of this study showed that the body weight, body weight gain, and body size of male Kerinci ducks were significantly different (P <0.05) higher that of females. Body weight gain at the age of 1-2 months was significantly different (P<0.05) higher than DOD-1, 2-3, and 3-4 months. DOD weight affects body weight. The highest correlation was found between DOD weight and body weight at 1 month of age. Conclusion: DOD weight, body weight, body weight gain, and body sizes of male Kerinci ducks were higher than females. DOD weight has the highest correlation with body weight at 1 month of age. Body size markers in male and female Kerinci ducks are chest circumference. The body shape of the male Kerinci duck is head height, while in the female is tibia length.Key words :  Male, female, quantitative, regression, and corelation.